Contamination And Health Risk Assessment Of Heavy Metals Form A Typical Pb-zn Smelter In Northwest China - Hu, Yantao; Wu, Defeng; Liu, Jinbao; Yan , Chaofan; Sun, Jiangfeng (Bangladesh Journal of Botany, 2023)
Soil contamination by heavy metals due to metal smelting activities poses a serious threat to the ecological environment and to human health, as it is considered to be one of the most significant sources of soil pollution. The objective of this study was to analyze the pollution status and human health risks of heavy metals emitted from metal smelting activities of a Pb-Zn smelter. The results of mean values of Zn, Pb, Cd, Cr, Cu and Mn should be incorporated and mention the status in respect to background value. Contamination levels of heavy metals were evaluated using the potential ecological risk index (RI). Possible human health risks were assessed using the health risk assessment model developed by the US EPA. The results showed that the soils are seriously polluted, and migrated down the soil vertical profile. The index of RI indicated a very high potential ecological risk overall in the entire study area, especially for Cd. The health risk analysis showed that adults and children are exposed to significant non-carcinogenic health risks, and there are higher non-carcinogenic health risks for children than for adults. Additionally, the carcinogenic risks of Cr were higher than those of Cd for the two population groups, and children were more susceptible than adults. These results are useful for management, prevention, control and remediation of heavy-metal contamination. Meanwhile, this research provides methods, experiences, and reference to other study of similar heavy-metal soil pollution. Bangladesh J. Bot. 51(4): 995-1015, 2022 (December) Special